Factors Related to the Depression of Health Workers During the Covid-19 Pandemic - Rejo Rejo; Dewi Arradini; Aquartuti Tri Darmayanti; Aris Widiyanto; Joko Tri Atmojo (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Previous studies have reported psychological disorders experienced by health workers such as anxiety, stress and depression during a pandemic will leave trauma that can last 1 - 3 years afterward. The systematic review study of the causes of depression from various countries can be an effort to determine prevention, treatment and rehabilitation measures for medical personnel who experience depression due to COVID-19 in Indonesia. Systematic searches were carried out in June - July 2020 through PubMed, Google Scholar, NIH, CDC, and Science Direct. Keywords: “COVID 19 and depression and Health workers” and “COVID 19 and depression”, “COVID 19 and depression and Health workers and factors associated” and “COVID 19 and depression and review”. The critical assessment of the article is carried out by the authors of all authors. There were 8 articles that met the inclusion criteria involving 16,107 health workers from around the world. Most of depression is caused by changes in work patterns that are increasingly busy, dense, risky, and also draining the mind and energy of health workers, especially those working on the front lines. Fear of contagion also dominates the factors that cause depression.